Meeting Scheduling Assembles Children in the Rectangular Forest - Tawfik, Ahmed; Alanai, Hijaz (2009)
This paper examines the implications of formalizing meeting scheduling as a spatiotemporal negotiation problem. In particular, the “Children in the Rectangular Forest” (CRF) canonical model is applied to meeting scheduling. By formalizing meeting scheduling within the CRF model, a generalized problem emerges that establishes a clear relationship with other spatiotemporal distributed scheduling problems. The paper also examines the implications of the proposed formalization to meeting scheduling negotiations. A protocol for meeting location selection is presented and evaluated using simulations.